(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Formulating questions is an essential skill that students must acquire to achieve proficiency in science. The 5E Learning Cycle (Engage, Explore, Explain, Elaborate, and Evaluate) plays a crucial role in this journey, allowing students to build their understanding over time. Thirty-four junior high school students learned the solar system using the 5E learning model. At the Cycle I, students’ ability to formulate questions was mainly at C1 and C2 (43%), C3 and C4 (7%), with no result at C5. However, in cycle II, there was a significant improvement in students’ ability to formulate questions, highlighting the beneficial feature of the 5E Learning Cycle in enhancing students’ questioning skills from lower to higher cognitive levels.